Living through pelvic radiotherapy:A mixed method study of self-care activities and distressful symptoms. Issue 3 (June 2015) - Jakobsson, Sofie; Ekman, Tor; Ahlberg, Karin
Abstract Purpose To explore patients' experience of their illness when undergoing pelvic radiotherapy by describing the presence and severity of distressful symptoms and to explore initiated self-care activities in response to illness and symptoms. Methods A mixed-method study was performed which included a core qualitative dataset and a supplementary quantitative dataset. Twenty-nine women undergoing five weeks of radiotherapy were prospectively interviewed during five weeks of treatment in order to capture experiences, distressful symptoms and quality of life during treatment. Grounded theory formed collection and analysis of the qualitative dataset and statistics were used to analyze the quantitative dataset. Results A maintained self-identity was concluded as being central during the trajectory of treatment. Initiated self-care activities served to alleviate physical, emotional, and social suffering; helping the respondents keep their integrity and sense of self. Previous life experiences influenced the process of being able to maintain self-identity. The gastrointestinal symptoms and pain caused most distress. Conclusions In order to be able to maintain self-identity patients endure treatment by focusing on symptoms, on getting cured and on their self-image. Several distressful symptoms implied social limitations and a sense that the body would not take the strain. The result of this study can help health care professionals to gain a better understanding of the struggle to endure pelvic radiotherapy. Further, health care professionals should be more proactive in alleviating their patients' distressful symptoms. The results imply that previous life experiences should precede initiated interventions because these life experiences affect the patients' self-care activities.